Genetic Ancestry, Intrinsic Tumor Subtypes, and Breast Cancer Survival in Latin American Women - Alves Da Quinta, Daniela Belén (2025)
This study investigates the relationship between genetic ancestry, breastcancer subtypes, and survival outcomes among 951 locally advanced breastcancer cases from Argentina, Brazil, Chile, Mexico, and Uruguay, participatingin the Molecular Profile of Breast Cancer Study. Array-basedgenotyping and ADMIXTURE analysis were used for genetic ancestryevaluation. Breast cancer subtypes were defined by IHC and the geneexpression–based PAM50 algorithm. The distribution of genetic ancestry,including European, Indigenous American (IA), African (AFR), and EastAsian components, revealed a heterogeneous genetic admixture acrosscountries, with the highest IA ancestry observed in Chile (30.9%) andMexico (30.8%). Testing the relationship between genetic ancestry andbreast cancer subtypes demonstrated that a 10% increase in Europeanancestry was significantly associated with a 14% decrease in the odds ofdeveloping HER2-enriched breast cancer, after adjustment by age, nodalstatus, and the AFR component (adj. P ¼ 0.021, luminal A as reference).Accordingly, a 10% increase in IA ancestry was associated with a 21%increase in the probability of having HER2-enriched breast cancer (adj.P ¼ 0.022). IA ancestry also significantly increased overall survival afteradjustment by age, nodal status, and AFR ancestry, although this result iscontroversial and may be affected by the size and heterogeneity of theMolecular Profile Breast Cancer Study cohort. Our research confirmsprevious findings of a high prevalence of HER2-dependent breast tumorsamong Hispanic/Latina women and strengthens the hypotheses of theexistence of either population-specific genetic variant(s) or of otherancestry-correlated factors that impact HER2 expression in breast cancerconsistently across different Latin American regions.